Distance by Degrees: Translating A Portrait of the Artist as a Young Man - Galindo, Caetano Waldrigues (ABEI Journal, 2016)
This article aims to present a personal view of the challenges involved in a new translation of Joyce’s first novel to Brazilian Portuguese, which will be the fifth to be published in Brazil since the pioneer work of JoséGeraldo Vieira in 1945. The category of “distance” will be employed to nuance the ideas of “domesticating” and “foreignizing” throughout the text, trying to demonstrate not only that the core of Joyce’s aesthetic project, as it can be seen in this novel, already questions stable positions and purely polar oppositions, but also that it posits possible solutions.Keywords: Translation; James Joyce; Lawrence Venuti